A proposed mother-friendly childbirth model for Taiwanese women and obstetricians' attitudes toward it - Yi-Ping Li; Shin-Yu Lin; Chih-Hsin Yeh; Heng-Cheng Hsu; Ya-Ling Yang; Chien-Nan Lee; Su-Chen Kuo (Elsevier, 2015)
Objective: Pleasant and humane childbirth is every mother's wish. The objective of this study was to propose a practicable mother-friendly childbirth model tailored to Taiwanese women in order to improve the quality of perinatal care and maternal satisfaction. Material and methods: In this study, the guidelines of several countries were systematically reviewed, and a standard set of clinical guidelines were established by a focus group. In addition, a total of 172 Taiwanese obstetricians were visited, and a cross-sectional study of these obstetricians' attitudes toward the practicality and effectiveness of the model was performed using questionnaires. Results: A total of 10 suggestions were developed for this woman-friendly childbirth model, including: (1) intermittent fetal monitoring for low-risk pregnancy, (2) no routine enema, (3) no routine perineal shaving, (4) no routine restricted oral intake, (5) no routine parenteral fluid support, (6) no routine elective amniotomy, (7) nonpharmacological pain management, (8) upright position during childbirth, (9) delayed pushing, and (10) restrictive episiotomy. Taiwanese obstetricians approved of no routine oral intake restriction and providing nonmedical pain relief. The majority of obstetricians disagreed that perineal shaving and routine elective amniotomy were necessary, and agreed to modify their practice according to the suggestions. Suggestions were still being debated, such as no routine parenteral fluid support, using an upright position for childbirth, and delayed pushing. Intermittent fetal monitoring for low-risk pregnancy, no routine enema, and restrictive episiotomy were questioned by many Taiwanese obstetricians. Conclusion: Several suggestions were made in this model. However, there was still no consensus of Taiwanese obstetricians. More evidence for the advantages and disadvantages of the various suggestions was needed to convince Taiwanese obstetrician to modify their routine practice.